2022
DOI: 10.1002/14651858.cd015207
|View full text |Cite
|
Sign up to set email alerts
|

Replacing salt with low-sodium salt substitutes (LSSS) for cardiovascular health in adults, children and pregnant women

Abstract: Background Elevated blood pressure, or hypertension, is the leading cause of preventable deaths globally. Diets high in sodium (predominantly sodium chloride) and low in potassium contribute to elevated blood pressure. The WHO recommends decreasing mean population sodium intake through effective and safe strategies to reduce hypertension and its associated disease burden. Incorporating low‐sodium salt substitutes (LSSS) into population strategies has increasingly been recognised as a possible sodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 154 publications
0
51
0
1
Order By: Relevance
“…[5][6][7] Additionally, potassium-containing salts have been used as substitutes for sodium. [8][9][10] Many studies have shown that high potassium intake may lower blood pressure and CVD risk partly, [11][12][13] and high potassium intake may mitigate the negative impacts of high sodium intake. 14 Cognitive impairment is linked to cardiovascular risk factors in the general population, 15 and diet is considered an important factor in cognitive function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] Additionally, potassium-containing salts have been used as substitutes for sodium. [8][9][10] Many studies have shown that high potassium intake may lower blood pressure and CVD risk partly, [11][12][13] and high potassium intake may mitigate the negative impacts of high sodium intake. 14 Cognitive impairment is linked to cardiovascular risk factors in the general population, 15 and diet is considered an important factor in cognitive function.…”
Section: Introductionmentioning
confidence: 99%
“…Properly managing sodium intake is a highly effective way to significantly reduce the risk of cardiovascular disease, and dietary sodium intake has been considered a common modifiable risk factor for hypertension 5–7 . Additionally, potassium‐containing salts have been used as substitutes for sodium 8–10 . Many studies have shown that high potassium intake may lower blood pressure and CVD risk partly, 11–13 and high potassium intake may mitigate the negative impacts of high sodium intake 14 …”
Section: Introductionmentioning
confidence: 99%
“…However, these trials excluded people known to be at high risk of hyperkalaemia, such as people with chronic kidney disease, diabetes or on potassium-sparing medications. Pooled analysis of seven trials included people possibly at risk of hyperkalaemia demonstrated a small increase in serum potassium with a mean difference 0.12 mmol/L higher in those using LSSS [33]. The risk versus benefits of salt substitutes in moderate-to-advanced chronic kidney disease population will need further evaluation.…”
Section: Salt-restricted Dietmentioning
confidence: 99%
“…The team published the results in the Cochrane Database of Systematic Reviews in August 2022. 3 On the basis of pooled data from ≈2 dozen randomized controlled trials that enrolled nearly 21 000 people, most of whom had elevated blood pressure, the researchers found an association between the substitutes and reduced blood pressure. They found that using salt substitutes reduced systolic blood pressure by an average of 4.76 mm Hg and diastolic blood pressure by 2.43 mm Hg.…”
Section: Salt Substitutesmentioning
confidence: 99%